Enhancement of transient erythropoietin protein expression by valproic acid in CHO‐K1 suspension adapted cells - Yana Rubiyana; Retno Damajanti Soejoedono; Adi Santoso (Indonesian Journal of Biotechnology, 2020)
Erythropoietin (EPO) is a therapeutic protein that is widely used to increase red blood cell production in chronic kidney failure. EPO protein can be produced quickly with a transient gene expression system (TGE). However, the titer produced using TGE is usually lower than the stable gene expression system (SGE). It has been known that TGE can be improved by histone deacetylase inhibitors (iHDACs) such as valproic acid (VPA). This study was conducted to examine the VPA effect on EPO protein expression in CHO‐K1 suspension adapted cells and to find the optimum concentration of VPA on transient EPO protein production. EPO proteins was quantified using the enzyme‐linked immunosorbent assay (ELISA) method. The optimization of VPA concentrations showed that VPA increased the EPO protein yield by up to 2‐fold in transient EPO production, and the optimum concentration of VPA was 4 mM. VPA optimization was very helpful to obtain the maximum increase in the transiently expressed protein. Furthermore, this study can be used as a model to produce EPO proteins or other recombinant proteins rapidly with TGE of CHO‐K1 suspension adapted cells.